A Case for Disrupting Coloniality in U.S. Academia: Towards Collaborative Knowledge Production and Decolonial Feminist Epistemologies (abstract accepted) - Dell'Orso, A. (Eleventh Social Science Methodology Conference of RC33, 2025)
My PhD thesis aims to work with students from a university student organization to identify and challenge coloniality in U.S. academia, specifically within university curricula, student organizing, and/or policy structures, and to foster decolonial feminist epistemologies. The study aspires to encourage critical research that engages with power structures to decolonize and democratize the research process and inspire actions for transformative social change and collective liberation. U.S. universities have historically and presently aided in colonialism and continue to reproduce violence , thus, all research can either associate with or against colonialism. Because universities are a key site for knowledge production, it is also an ideal site for challenging the traditional researcher-subject divide. I intend to do so by involving participants to collectively create knowledge rather than extract it from them. This route proposes democratizing knowledge generation and ownership and making the research process itself a form of activism. Participatory action research may allow for developing the decolonial feminist epistemologies that this research seeks to explore. Further, a collaborative research process may directly contribute to social change, certifying that the knowledge produced is not just theoretical but truly has practical implications for liberation movements. Five main theoretical focal points – whiteness, settler colonialism and coloniality, decoloniality and decolonization, abolition-democracy, and liberation as a praxis – together provide a robust foundation for analyzing how university colonial legacies are perpetuated, how to challenge them as a researcher and how students might challenge them collectively. Ten main concepts are central to this study: student activism and organizing, critical consciousness, collaborative knowledge production, intersecting systems of oppression, status quo, violence, social action, justice, social change, and collective liberation. The literature review will feature empirical studies on student activism and collaborative knowledge production amongst students in higher education to formulate the participatory action research methodology.